Connecting Christianities : World Christianity and Mission in the Twenty-First Century - Leith, Jenny,; Swamy, Muthuraj, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
How to understand and practice World Christianity and mission in the twenty-first century? What does World Christianity mean to an ordinary Christian in their everyday life? In what ways do Christians belong to a global Christian community? This book engages with these questions by offering a critical perspective on prevalent notions of World Christianity. In a context where World Christianity is often understood as an effort to make the whole world Christian or as Christianity of the global south, this book emphasises the importance of global connections in Christianity. This way of thinking about World Christianity not only opens up new horizons in scholarship but also has implications for the practice of everyday Christian mission in the contemporary context: through building connections with fellow Christians from different denominational and geographical backgrounds, with people of other religions and traditions, and with the wider society.